Influence Style Life and Image Brand to Decision Purchase Shoe Adidas in Depok - Nasit Ramadan Sesareanto; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effect of lifestyle and brand image on purchasing decisions of Adidas shoes in Depok. This study uses primary data withdata collection methods through questionnaires distributed to 100 visitors to the Adidas store in Depok. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 26 programs. From the results of the analysis there is a positive and significant influence on lifestyle and brands image variables on purchasing decisions. The writer hopes that PT. Adidas AG in Depok can try to improve Purchasing Decisions by taking into account the influence of Lifestyle and Brand Image.